Derivation and Validation of ESC-0/1-h Algorithm for High-Sensitivity Troponin T and I in Cancer Patients - Bima, Paolo; Lopez-Ayala, Pedro; Koechlin, Luca; Morello, Fulvio; Boeddinghaus, Jasper; Dimitrova, Mihaela; Spagnuolo, Carlos C; Kaplan, Emel; Nestelberger, Thomas; Glaeser, Jonas; Wildi, Karin; du Fay de Lavallaz, Jeanne; et al. (JACC. Advances, 2025)
BACKGROUND: The diagnostic performance of high-sensitivity cardiac troponin T/I (hs-cTnT/I) and the efficacy of the European Society of Cardiology (ESC) 0/1-h hs-cTnT/I algorithms for the early diagnosis of non-ST-elevation myocardial infarction are lower in cancer patients. OBJECTIVES: The authors aimed to derive new cutoffs for ESC 0/1-h hs-cTnT/I algorithms optimized for use in patients with active or past cancer. METHODS: Patients presenting with suspected non-ST-elevation myocardial infarction to the emergency department enrolled in an international multicenter study were analyzed. Final diagnoses were centrally adjudicated by 2 independent cardiologists according to the fourth universal definition of myocardial infarction. External validation was performed in 2 independent cohorts. RESULTS: Among 541 eligible cancer patients, cancer-optimized ESC 0/1-h hs-cTnT cutoffs, <8 ng/L at presentation (if chest pain onset >3 hours) or <14 ng/L if 0/1 h-delta is <3 ng/L for rule-out and ≥54 ng/L or 0/1-h delta ≥4 ng/L for rule-in, increased the efficacy vs the current cutoffs from 58.6% (95% CI: 54.4-62.7) to 68.0% (95% CI: 64.0-71.8; P < 0.001). Sensitivity and specificity remained high and comparable. Similarly, among 516 eligible patients, cancer-optimized ESC 0/1-h hs-cTnI-Architect cutoffs, <7 ng/L at presentation (if chest pain onset >3 hours) or <10 ng/L if 0/1-h delta is <3 ng/L for rule-out and ≥61 ng/L or 0/1-h delta ≥5 ng/L for rule-in, increased the efficacy vs the current cutoffs from 59.3% (95% CI: 55.0-63.5) to 78.9% (95% CI: 75.2-82.2; P < 0.001). Sensitivity and specificity again remained high and comparable. Findings were confirmed in internal and external validation cohorts (n = 130 and n = 195 patients, respectively). CONCLUSIONS: Cancer-optimized ESC 0/1-h hs-cTnT/I algorithm cutoffs increased efficacy maintaining high safety.
Keywords: diagnosis; cardiac troponin; cancer; cutoffs; myocardial infarction; prognosis